Relationship between the radial dynamics and the chemical production of a harmonically driven spherical bubble - Kalmár, Csanád; Klapcsik, Kálmán; Hegedűs, Ferenc (Ultrasonics sonochemistry, 2020)
•Chemical production and collapse strength of bubbles are related closely.•Collapse strength cannot characterize the intensity of chemical processes alone.•Chemical output heavily depends on bubble size.•Chemical output can be approximated from dynamical features of bubbles. The sonochemical activity and the radial dynamics of a harmonically excited spherical bubble are investigated numerically. A detailed model is employed capable to calculate the chemical production inside the bubble placed in water that is saturated with oxygen. Parameter studies are performed with the control parameters of the pressure amplitude, the forcing frequency and the bubble size. Three different definitions of collapse strengths (extracted from the radius vs.time curves) are examined and compared with the chemical output of various species. A mathematical formula is established to estimate the chemical output as a function of the collapse strength; thus, the chemical activity can be predicted without taking into account the chemical kinetics into the bubble model. The calculations are carried out by an in-house code exploiting the high processing power of professional graphics cards (GPUs). The results shown that chemical activity can be approximated qualitatively from the values of relative expansion. This could be helpful in order to optimise chemical output of sonochemical reactors either from measurement data or simulations as well.